2018
DOI: 10.1109/tccn.2018.2835460
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Models for Wireless Signal Classification With Distributed Low-Cost Spectrum Sensors

Abstract: This paper looks into the modulation classification problem for a distributed wireless spectrum sensing network. First, a new data-driven model for Automatic Modulation Classification (AMC) based on long short term memory (LSTM) is proposed. The model learns from the time domain amplitude and phase information of the modulation schemes present in the training data without requiring expert features like higher order cyclic moments. Analyses show that the proposed model yields an average classification accuracy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
368
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 624 publications
(372 citation statements)
references
References 18 publications
2
368
0
2
Order By: Relevance
“…Considering channel interference, the CNN structure also achieves a considerable classification accuracy [13]. In addition to the CNN-based models, the Long Short-Term Memory (LSTM) architecture with time-dependent amplitude and phase information can achieve the state-of-theart classification accuracy [18]. To reduce the training time of deep learning models, different subsampling techniques are investigated in [17] which reduce the dimensions of the input signals.…”
Section: A Deep Learning In Radio Modulation Classificationmentioning
confidence: 99%
“…Considering channel interference, the CNN structure also achieves a considerable classification accuracy [13]. In addition to the CNN-based models, the Long Short-Term Memory (LSTM) architecture with time-dependent amplitude and phase information can achieve the state-of-theart classification accuracy [18]. To reduce the training time of deep learning models, different subsampling techniques are investigated in [17] which reduce the dimensions of the input signals.…”
Section: A Deep Learning In Radio Modulation Classificationmentioning
confidence: 99%
“…is an appealing technique for environment identification and transmitter identification. Inspired by the strengths of the long short term memory (LSTM), deep learning-based signal classification is developed [14]. The framework is trained to classify 11 typical modulation Rectified Linear Unit (ReLU) function is introduced to activate all the hidden layers.…”
Section: Overview Of Deep Learning For Wireless Communicationmentioning
confidence: 99%
“…The effect of digital RSSI filtering, here obtained by an 802.15.4-emulator, is most devastating in terms of information loss. Due to low-pass filtering (LPF) effect, not only it wipes out the information on signal envelopeinhibiting modulation-based identification (such as [10]), but also caps time-resolution-dampening the information gain of sampling frequencies above f r = 7.8 kHz. This, in turn, reflects on the inability to capture short interference bursts and inter-frame spaces, such as the 802.11 DCF inter-frame space (DIFS).…”
Section: B Energy Sampling With 802154 Hardwarementioning
confidence: 99%
“…Using specialized hardware, such as WLAN cards and SDRs, for protocol-free IDI has also been investigated in many studies, e.g., [10], [18], [19] and references therein. As this hardware can ensure high sampling frequency and highresolution I/Q data, the benefit of more complex classifiers (e.g., deep learning-based [10]) increases and higher accuracy is generally achieved. However, we have shown that, even with limited sensing resolution and lightweight supervised learning, COTS IoT nodes can reach the same-level of accuracy in realtime.…”
Section: Related Workmentioning
confidence: 99%